Russian-German Political Relations in 1991–2021 in Modern Russian Historiography - O. E. Terekhov (Вестник Кемеровского государственного университета, 2022)
The article deals with modern Russian historiography of the political relations between Russia and Germany in 1991– 2021. Due to the vastness of the research scope, the paper covers only the major trends in the Russian-German political relations in the Russian historiography. The work relied on the problem-chronological method that made it possible to consider the topic in diachronic and synchronic perspective, simultaneously revealing its temporal and problematic components. The research featured works by contemporary Russian historians, political scientists, and economists on the political relations between the Russian Federation and the Federal Republic of Germany. The thirty-year history of relations between the united Germany and the Russian Federation was full of events and can be divided into several periods. As a result of the historiographical process, the modern Russian historiography consists of three stages, which partially coincide with the chronology of direct political relations between Russia and Germany. The assessment of the Russian-German relations in modern historiography directly depends both on their conjecture and the historical and political context.